The Tangi - Wharemate, Hannah (Te Kaharoa, 2021)
The first day, it was dark, the clouds hung over us, not only the rain clouds but the cloud of sadness that lingered since that last day with him. We stood huddled at the gate, hiding from the rain under umbrellas but also from the eyes of the crowds of people watching us in our grief. The kaumatua of the marae signaled it was time, time for us to take him inside the Marae where he would lay, where we would share him with all the others who had come to be with him.